[The Great grey Shrike Lanius excubitor L. of the Arrigoni degli Oddi's ornithological collection at the Museo Civico di Zoologia, Rome (Italy)] - Fraticelli, Fulvio; Marangoni, Carla (Rivista Italiana di Ornitologia, 2018)
[Lanius excubitor is a polymorphic species with 12 subspecies. In the last years the taxonomy of this species has been reviewed several times. According to the literature, in Italy Lanius excubitor is a regular migrator, wintering and irregular nesting, occurring with three subspecies: L. excubitor excubitor, L. e. homeyeri and L. e. sibiricus. This paper aims at reviewing the subspecies actually occurring in Italy by analyzing the specimens preserved in the Arrigoni degli Oddi's collection at the Museo Civico di Zoologia in Rome (Italy). The morphometrics and colouring of 66 specimens were examined in relation to the most recent literature data. This review allowed to demonstrate that all specimens described as L. e. homeyeri in this collection have to be attributed to the nominate subspecies; only the specimen described as L. przelwaskii (now L. e. leucopterus) is a true L. e. homeyeri. According to these data, the ssp. homeyeri must be considered very rare in Italy, contrarily to some previously reported information. Specimens ascribed to L. borealis sibiricus do not show the characters of this subspecies, consequently they should not be included in the check list of Italian species.] [Article in Italian]